2019
DOI: 10.1016/j.toxrep.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Essential trace elemental levels (zinc, iron and copper) in the biological samples of smoker referent and pulmonary tuberculosis patients

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…The study shows that the copper level higher in TB patients than controls. This finding was matched with (33) who mentioned the level of copper was higher in the biological samples of pulmonary Tuberculosis patients as compared to control (p < .001). This finding also matched with (34) who mentioned that there was a significant increase in serum copper levels of TB patients.…”
Section: Copper Concentrationsupporting
confidence: 80%
“…The study shows that the copper level higher in TB patients than controls. This finding was matched with (33) who mentioned the level of copper was higher in the biological samples of pulmonary Tuberculosis patients as compared to control (p < .001). This finding also matched with (34) who mentioned that there was a significant increase in serum copper levels of TB patients.…”
Section: Copper Concentrationsupporting
confidence: 80%
“…Also, we measurement the levels of albumin and total protein in both groups that were recruited; we found that after 6 months of taking Zn, the albumin concentration was higher and total protein were markedly lower compared to placebo group. Some studies declared possible reasons to the low serum Zn and albumin and total protein in patients with TB infection may be nutritional factors, enteropathy, and acute phase reactant proteins (17)(18)(19). Immune factors such as interleukin-6 and TNF-α are causes to induction of acute phase reactant proteins in the liver, which can lead to decrease of serum albumin also, reason to significant changes in the serum levels of some essential trace elements and total protein (20).…”
Section: Discussionmentioning
confidence: 99%
“…For a comprehensive presentation of instrumental conditions and methodological subtleties, we provide detailed data in Supplementary Table S1. In addition, for a holistic understanding of the methods used, we discussed (Nizamani et al 2019; Oan Muhammad Sahito & Rahoojo 2022) in our previous study.…”
Section: Apparatus Reagents and Glasswarementioning
confidence: 99%